1994
DOI: 10.1111/j.1365-2362.1994.tb01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bile salt and phospholipid hydrophobicity on lithogenicity of human gallbladder bile

Abstract: Abstract. Increased biliary bile salt and phospholipid hydrophobicity may promote nucleation of cholesterol crystals and gallstone formation. We therefore compared bile salt composition (determined by gasliquid chromatography) in patients with cholesterol (n = 35) and pigment (n = 16) gallstones (group A). Bile salt composition and cumulative bile salt hydrophobicity index were not different between both stone types. Hydrophobicity index or YO of individual bile salts did not correlate with cholesterol saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…2 g dL ÿ 1 ) with a very unphysiological composition (97 . Third, two recent studies found a positive correlation of percentage of deoxycholate with cholesterol saturation index as well as with nucleation time in bile [22,24] (a third study from our group, however, did not find such a correlation [17]). The relevance for human gallstone formation therefore was uncertain.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…2 g dL ÿ 1 ) with a very unphysiological composition (97 . Third, two recent studies found a positive correlation of percentage of deoxycholate with cholesterol saturation index as well as with nucleation time in bile [22,24] (a third study from our group, however, did not find such a correlation [17]). The relevance for human gallstone formation therefore was uncertain.…”
Section: Discussioncontrasting
confidence: 52%
“…These forms (filaments, tubules, spirals) might be metastable intermediates of-probably anhydrous-cholesterol in the process of formation of the classical triclinic cholesterol monohydrate crystals [3]. Moreover, our group [17] and Angelico et al [18] found that molecular composition and cumulative hydrophobicity of the phospholipid mixture in human bile are regulated within a very narrow range and do not correlate with nucleation time of cholesterol crystals. Although it was previously suggested that phospholipid molecular composition might be important in this respect, this was based on experiments in very dilute model biles (TLCo 1 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Research interest during the last two decades has been focused on the metabolism of biliary lipids and its relationship to gallstone formation (3,4). It has become evident that a disturbed metabolism of cholesterol and/or bile salt constitutes a major factor in gallstone formation (5,6). In bile, bile salts, phospholipids (PLs), and cholesterol are the major lipid components (7) and, depending on their relative concentrations, they interact to form several different biliary lipid micelles (8).…”
mentioning
confidence: 99%
“…Increasing biliary UDCA, in turn, results in a decreased hepatic secretion of biliary cholesterol and the formation of unsaturated gallbladder bile (i.e. containing less cholesterol in solution) with a cholesterol saturation index of less than 1 (81-83) (Figure 2). This step represents a key factor in initiating the process of dissolution of cholesterol crystals and gallstones.…”
Section: Medical Treatments Of Gallstone Diseasementioning
confidence: 99%